Maternal coping, appraisals and adjustment following diagnosis of fetal anomaly. (3rd September 2013) - Horsch, Antje; Brooks, Chloe; Fletcher, Helen
ABSTRACT Objective So far, associations between appraisals, maternal adjustment and coping following diagnosis of fetal anomaly have not been investigated in women who continue with their pregnancy. Method This study measured maternal coping and adjustment after and appraisal of a diagnosis of fetal anomaly in 40 mothers who had continued with their pregnancy using a cross‐sectional questionnaire design. Results Based on retrospective reporting, 35% of participants met full diagnostic criteria for post‐traumatic stress disorder after having received the diagnosis. Women were significantly more depressed (p < 0.001) and anxious (p < 0.001) and reported significantly less positive affect (p < 0.05) after having received the diagnosis in comparison to the time after childbirth. There were no significant differences between emotion‐focused and problem‐focused coping. Stressful life events, women's age, number of people providing support and problem‐focused coping explained 57.6% of variance in anxiety and depression after childbirth. Satisfaction with social support, emotion‐focused coping and problem‐focused coping significantly explained 40.6% of variance in positive affect after childbirth. Conclusion Following a prenatal diagnosis and for the remainder of their pregnancy, particular attention should be paid to older mothers, those experiencing additional stressful life events and those who are socially isolated, as these women may experience greater distress after childbirth. © 2013 John Wiley & Sons, Ltd.